The binding orientations of structurally-related ligands can differ; A cautionary note. (June 2017) - Ruepp, Marc-David; Wei, Hao; Leuenberger, Michele; Lochner, Martin; Thompson, Andrew J.
Abstract: Crystal structures can identify ligand-receptor interactions and assist the development of novel therapeutics, but experimental challenges sometimes necessitate the use of homologous proteins. Tropisetron is an orthosteric ligand at both 5-HT3 and α7 nACh receptors and its binding orientation has been determined in the structural homologue AChBP (pdbid:2WNC ). Co-crystallisation with a structurally-related ligand, granisetron, reveals an almost identical orientation (pdbid; 2YME). However, there is a >1000-fold difference in the affinity of tropisetron at 5-HT3 versus α7 nACh receptors, and α7 nACh receptors do not bind granisetron. These striking pharmacological differences prompt questions about which receptor the crystal structures most closely represent and whether the ligand orientations are correct. Here we probe the binding orientation of tropisetron and granisetron at 5-HT3 receptors by in silico modelling and docking, radioligand binding on cysteine-substituted 5-HT3 receptor mutants transiently expressed in HEK 293 cells, and synthetic modification of the ligands. For 15 of the 23 cysteine substitutions, the effects on tropisetron and granisetron were different. Structure-activity relationships on synthesised derivatives of both ligands were also consistent with different orientations, revealing that contrary to the crystallographic evidence from AChBP, the two ligands adopt different orientations in the 5-HT3 receptor binding site. Our results show that even quite structurally similar molecules can adopt different orientations in the same binding site, and that caution may be needed when using homologous proteins to predict ligand binding. Highlights: The drugs granisetron and tropisetron are structurally similar. Crystals of them bound to AChBP suggest they have similar binding orientations. At 5-HT3 R, the effects of mutagenesis indicate that their orientations differ. SAR on both of these drugs also supports different orientations.